The Welfare State and Economic Growth – Econometric Evidence from Germany - Reichel, Richard (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2022)
This paper attempts to analyze the growth effects of social security expenditures in Germany from a time series perspective. Therefore, a regression model based on standard determinants of growth is specified and estimated as a vector error correction model. Results show that there is a bidirectional relationship between growth and social security expenditures. In the short run, social security expenditures and growth rates are inversely related. Lower or even negative growth rates cause higher expenditures of the welfare state. In the long run, there is also an inverse relationship, but the direction of causality changes. Higher social security spending triggers lower growth rates. Robustness tests confirm the stability of the results.